Socio-Cultural, Educational, and Psychological Barriers in ESL Learning: A Qualitative Study of Senior High School Students - Juharto L. Usop (Randwick International of Education and Linguistics Science Journal, 2024)
This qualitative study explores the complex issues faced by the Senior High School students in learning ESL. Using the interviews and focus group discussions, this study aims at finding out the students’ experience, perception and challenges relating to their English accent. Ten male and twenty female students from the socio culturally and linguistically diverse school in Cotabato City Division volunteered for the study, offering information on the socio cultural, educational, and psychological aspects affecting their ESL learning during the academic year 2022-2023. The study shows that low students’ interactions in English beyond the classroom, the preferred use of students’ native language patterns, and inadequate amounts of exposure to English contexts are specific socio-cultural factors. Learning difficulties include; the imbalance in teachers’ competency, instruction, and teaching methods, and student supplies. On the psychological level, students have anxiety, unstable motivation, and problems with self-efficacy, which provides a meaningful addition to learners’ difficulties. Thus, this study recommended the need to tackle these challenges by increasing the training of teachers, developing quality teaching and learning materials, and providing effective learning conditions. These include promotion of English in contextual setting, computer aided instruction, offering counseling and psychological services to boost the learners’ morale. The findings of this study are hoped to help educators, and relevant stakeholders understand the best practices on how to help ESL learner Senior High School Students to break barriers and succeed academically and in their future careers as the world becomes a global village.